2002
DOI: 10.1038/sj.onc.1205311
|View full text |Cite
|
Sign up to set email alerts
|

Mouse homologue of HOS (mHOS) is overexpressed in skin tumors and implicated in constitutive activation of NF-κB

Abstract: NF-kB transcription factor is activated upon ubiquitination and subsequent proteolysis of its inhibitor IkB. The phosphorylation-dependent ubiquitination is mediated by SCF E3 ubiquitin ligase. In this study, we identi®ed a novel murine F-box/WD40 repeat-containing protein, mHOS (a homologue of HOS/bTrCP2). mHOS eciently binds Skp1 protein (a`core' component of SCF ubiquitin ligase), and phosphorylated IkBa. We found that mHOS associates with SCF-ROC1 E3 ubiquitin ligase activity. We have also observed that mH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…An involvement of hTRCP in tumorigenesis has been recently proposed for skin, gastric, and colon cancer (39)(40)(41). In addition, deregulated hTRCP expression has been linked to other tumor promoting pathways such as down-regulation of the disc large tumor suppressor (hDlg; ref.…”
Section: Discussionmentioning
confidence: 99%
“…An involvement of hTRCP in tumorigenesis has been recently proposed for skin, gastric, and colon cancer (39)(40)(41). In addition, deregulated hTRCP expression has been linked to other tumor promoting pathways such as down-regulation of the disc large tumor suppressor (hDlg; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated levels of b-TrCP2 are also observed in a number of tumor tissue samples from the patients with primary prostate, breast and gastric cancers (Saitoh and Katoh, 2001;Spiegelman et al, 2002a). In addition, b-TrCP2 is overexpressed in chemically induced mouse skin tumors, and its overexpression (but not elevated IkB phosphorylation) coincides with the accelerated degradation of IkB in vivo, and constitutive activation of NF-kB signaling in mouse skin tumors (Budunova et al, 1999;Bhatia et al, 2002). These data indicate that overexpression of b-TrCP1/b-TrCP2 may represent a common trend in a variety of human and mouse tumors.…”
Section: Aberrations Of B-trcp In Tumorigenesismentioning
confidence: 98%
“…Nevertheless, these data should not be overinterpreted until the development of a suitable antibody for the analysis of endogenous b-TrCP1 localization. Conversely, whereas endogenous murine b-TrCP2 is predominantly found in the cytoplasm of the cells of mouse tissues (Bhatia et al, 2002), a putative role for b-TrCP2 in degradation of cytoplasmic proteins must be corroborated by studies in b-TrCP2 knockout animals. In addition, substrate specificity of b-TrCP may be a subject of tissue-and stimuli-specific regulation of their expression (see below).…”
Section: Regulation Of B-trcp Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of b-Trcp renders cells more susceptible to apoptotic cell death because of IkB accumulation but likely also because of the stabilization of other substrates, such as b-catenin, Emi1 and Cdc25A, which could potentially push cells out of quiescence, a state in which cells are more resistance to apoptosis. Bhatia et al (2002) found that the b-Trcp2 transcript is upregulated in chemically induced mouse papillomas and squamous cell carcinomas and this overexpression is associated with accelerated degradation of IkBa and constitutive activation of NF-kB. Moreover, b-Trcp1 overexpression in mouse mammary gland epithelium leads to increased ductal branching and elevated proliferation of the epithelial cells correlating with enhanced NF-kB activity (Y Kudo, D Guardavaccaro, P Gonzalez and M Pagano, unpublished results).…”
Section: Scf B-trcpmentioning
confidence: 97%